Calculation of Assimilation Process of Non-metallic Inclusions by Slag - Kalisz, Dorota (Journal of Casting & Materials Engineering, 2017)
This paper presents the results of calculating the phenomenon of the absorption of non-metallic precipitates in steel by slag. Calculations are made for the forces acting on the non-metallic particles in steel during the flow-out into the slag, depending on the particle radius and physicochemical properties of the liquid steel and slag. An analysis of the calculation results of capillary force acting on a particle in the vicinity of the steel-slag interface at changing surface energy values between the precipitates and slag shows that capillary force depends on the interfacial tension between the precipitates and slag only to a small degree.